Effects of guided breath exercise on complex behaviour of heart rate dynamics - Tavares, Bruna S. [UNESP]; de Paula Vidigal, Giovanna [UNESP]; Garner, David M.; Raimundo, Rodrigo D.; de Abreu, Luiz Carlos; Valenti, Vitor E. [UNESP] (Wiley, 2017)
Introduction: Cardiac autonomic regulation is influenced by changes in respiratory rate, which has been demonstrated by linear analysis of heart rate variability (HRV). Conversely, the complex behaviour is not well defined for HRV during this physiological state. In this sense, Higuchi Fractal Dimension is applied directly to the time series. It analyses the fractal dimension of discrete time sequences and is simpler and faster than correlation dimension and many other classical measures derived from chaos theory. We investigated chaotic behaviour of heart rate dynamics during guided breath exercises. Method: We investigated 21 healthy male volunteers aged between 18 and 30 years. HRV was analysed 10 min before and 10 min during guided breath exercises. HRV was analysed in the time and frequency domain for linear analysis and through HFD for non-linear analysis. Results: Linear analysis indicated that SDNN, pNN50, RMSSD, LF, HF and LF/HF increased during guided breath exercises. HFD analysis illustrated that between Kmax 20 to Kmax 120 intervals, was enhanced during guided breath exercises. Conclusion: Guided breath exercises acutely increased chaotic behaviour of HRV measured by HFD.
Keywords: autonomic nervous system; cardiovascular system; respiratory rate